Difference and differential equations with applications in queueing theory - Haghighi, Aliakbar Montazer; Mishev, D. P. (Dimiter P.) (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
"This book features a collection of topics that are used in stochastic processes and, particularly, in queueing theory. Differential equations, difference equations, and Markovian queues (as they relate to systems of linear differential difference equations) are presented, and the relationship between the methods and applications are thoroughly addressed"--
5.5.1. Transient Queue Length Distribution for M/M/1.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Queuing theory; Difference equations; Differential equations; Difference equations; Differential equations; Mathematics; Queuing theory; MATHEMATICS -- Probability & Statistics -- General; Difference equations; Differential equations; Queuing theory; Warteschlangentheorie; Differenzengleichung; Differentialgleichung; Electronic books